Pemodelan 3 Dimensi Volume Rembesan Polutan Sampah untuk Penentuan Lapisan Akuifer - Rahma Sahiruddin; Agustina Agustina; Ni Luh Mira Sukmawati; Muhammad Fajar; Rahma Hi Manrulu (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2022)
Research has been carried out with the title 3-dimensional modeling of the volume of waste pollutant seepage to create an aquifer layer at the Mancani Landfill, Palopo City. This study aims to determine the volume of waste pollutant seepage in the Mancani TPA Palopo City by knowing the depth of the air based on its resistivity value. Measurements were made with 5 tracks along the 200 meters using the Schlumberger configuration. The data is carried out using IP2Win Software to obtain resistivity values and depth and Voxler Software to obtain 3 Dimensional modeling, data interpretation based on resistivity tables. The results obtained are that the leachate at the Mancani landfill in Palopo City is at a depth of 1 - 4.5 meters with a resistivity value ranging from 11.00-23.39 Ωm and a seepage volume of 29,929 m3